MENINGKATKAN KESADARAN MASYARAKAT DALAM PENERAPAN PROTOKOL KESEHATAN MELALUI MEDIA SOSIAL DI KELURAHAN AEK MUARA PINANG KECAMATAN SIBOLGA SELATAN KOTA SIBOLGA - Afif Syarifudin Yahya; Helen T.W.M (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The lack of citizens awareness of Covid-19 has resulted in many people in Aek Muara Pinang Village infected with the corona virus, so it is necessary to make efforts to increase citizens awareness about the prevention of transmission of COVID-19 through social media to help the citizens to continue implementing health protocols in Aek Muara Pinang Village. This activity aims to increase citizens awareness in implementing health protocols. The method used is making educational videos, socializing around and distributing masks.The results of this activity indicate that Muara Pinang has started to become aware of implementing health protocols which are marked by a reduction in crowd places, and people have started wearing masks every time they do activities outside the home. Besides that the video making activity program is spread on social media accounts such as YouTube with a total number of publishers / viewers as many as 88, the number of publishers on Facebook accounts as many as 249, and the number of viewers on Tiktok accounts as many as 52